COLLABORATIVE GOVERNANCE DALAM KEBIJAKAN LINGKUNGAN (STUDI KASUS PEMANFAATAN LIMBAH KELAPA SAWIT DI KABUPATEN ROKAN HULU) - Adianto Adianto; Rendi Prayuda (Lembaga Administrasi Negara, 2018)
The research present describe the collaborative governance in environment policy in management waste of palm oil in Rokan Hulu regency. Rokan Hulu are one of regency in Riau Province that have a big potency in forestry especially about palm oil. In 2012 land of palm oil in Rokan Hulu are arround 208.475 Ha with production 525.079,93 miles CPO. Now days are 31 manufactured are productions of palm oil in 16 subdistrict. The research use the methode are qualitative methodes that analyze problem research by describe the subject and object conditions based on real fact. This research use location in Rokan Hulu regency. Researcher collect data from books, government regulation, jurnal, mass media, website and deep interview with informan head of village in Tuah Sakti Villages, Staff in PLBTG Tuah Sakti and society in Tuah Sakti Village. The conclusion of this research are collaborative governance are implemented in Rokan Hulu Regency are based on environment and supported with maintenance palm oil based on environment with program that held by Energy and Mineral Resources Ministry by independence village. Collaboration information are create a inhibition becaused changing the distirbution authority from regency to Province government. Conflict between PLTBG and PLN Bagan Batu, Mahato Sakti that have a difference region. It is caused a conflict between staff of PLBTG with PLN that have meets in forum but never get agreement.Keywords: collaborative governance, public policy and environment policy